2016
DOI: 10.1016/j.joca.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity-to-change and validity of semi-automatic joint space width measurements in hand osteoarthritis: a follow-up study

Abstract: Assessment of progression in hand OA defined by JSW measurements is possible, but performs less well than progression defined by JSN scoring. Therefore, the value of JSW measurements in hand OA clinical trials remains questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…studied the validity of semi-automatic JSW measurements using US findings and reported that progression in both semi-automatic JSW and conventional scoring methods showed associations with inflammatory US features at baseline (31). In the current study, we also found association between US findings and progression of semi-quantitative JSN scoring and semi-automated JSW measurements.…”
Section: Discussionsupporting
confidence: 74%
“…studied the validity of semi-automatic JSW measurements using US findings and reported that progression in both semi-automatic JSW and conventional scoring methods showed associations with inflammatory US features at baseline (31). In the current study, we also found association between US findings and progression of semi-quantitative JSN scoring and semi-automated JSW measurements.…”
Section: Discussionsupporting
confidence: 74%
“…For semi-quantitative score, the kappa values varied from slight in cartilage thickness 51 to substantial in osteophyte and synovitis 5,12 . For quantitative score, ICC was excellent in synovial hypertrophy 54 .…”
Section: Reliabilitymentioning
confidence: 96%
“…There were four inter-rater reliability studies for binary scores 50e53 , three for semi-quantitative scores 5,12,51 and one for quantitative scores 54 .The binary scoring system provided the kappa ranging from slight in cartilage thickness 51 to excellent in synovitis, effusion and osteophyte 52 . For semi-quantitative score, the kappa values varied from slight in cartilage thickness 51 to substantial in osteophyte and synovitis 5,12 .…”
Section: Reliabilitymentioning
confidence: 99%
“…The primary endpoint may be assessed either as radiographic change using semi-quantitative scoring systems such as the KL grading scale, which is a global OA scale, or the OARSI atlas, which assesses individual OA features [49]. Alternatively, change in quantitative joint space width (JSW) or progression quantified as joint space narrowing (JSN) and measured by conventional X-ray can be used [50]. However, JSW assessment has not been fully validated and the optimal analysis of JSW measurement to maximise sensitivity to change is to be determined.…”
Section: Study Conductmentioning
confidence: 99%